The impact of home-based call on sleep patterns and wellness in genetics and metabolism physicians compared with subspecialists - Kiley Boone Quintana; Ilana Miller; Debra S. Regier (Genetics in Medicine Open, 2024)
Purpose: With increases in precision medicine initiatives and genetically defined rare diseases, the genetics and metabolism workforce is necessary to provide around-the-clock care for patients. Here, we describe the impact that home-based call has on the geneticist and metabolist workforce. Methods: Physicians from 3 populations were self-identified (pediatric subspecialist, geneticist, metabolist) and completed a survey regarding the impact of home-based call service on their sleep and wellness. Results: Estimated sleep while serving on home-based call was reduced from 7.5 to 5.4 hours per night. Safety concerns were noted by geneticists and metabolists for themselves (55%) and their families (28%), similar to other subspecialists. Geneticists and metabolists were more likely than other pediatric subspecialists to be worried about their patient’s safety while on home-based call (48% vs 9%). Themes from open-ended questions regarding the impact of home-call included positive responses, decreased access to wellness activities, sleep exhaustion, impact on life responsibility, and impact on mood. Reported coping mechanisms included work-based initiatives, off-loading personal responsibility, and creating personal accommodations. Conclusion: Institutional-based supports for home-based call were endorsed by only 29% of respondents; thus, interventions at the institutional level would be expected to have a large effect on overall provider wellness.